Kidney disease impact on family survival of a sick person in Sri Lanka - A. Shashini Warnakulasooriya (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: In the mid-1990s, kidney disease was first reported from the Padaviya area; today, it is widespread throughout the dry zone. Most of those who fall income to this disease are farmers from economically disadvantaged communities. Consequently, the question of "how does kidney disease affect the family economy?" was chosen as the focus of the study. This study aimed to quantify the financial burden of kidney disease on rural Sri Lankan families. Methodology: This study employed a qualitative research approach. For this study, we employed a mix of primary and secondary sources. Primary data was collected from thirty families, and secondary data was gathered from scholarly articles, books, and reports. The research was conducted in the Mahadiwulwawa Grama Niladari division of the Madawachchiya neighborhood of the Anuradhapura district of SriLanka. The data were analyzed using a thematic approach. Findings: According to the results, kidney disease dramatically impacts a family’s standard of living and negatively affects every aspect of family income. Implications/Novel Contribution: The primary manifestation of kidney disease is its medi calization. In addition, it has far-reaching effects on individuals and communities. It is one of the country’s most pressing social problems, and it has had a profound impact on Sri Lankan culture. This study adds to the existing body of literature by elucidating the repercussions of kidney disease on family income. .